30.3k views
13 votes
Two step educations 3c - 6 = 12 ​

2 Answers

8 votes

Answer:

C = 6

Explanation:

Move all terms that don't contain C to the right side and solve.

User Victoria Agafonova
by
4.9k points
6 votes

Answer:

C=6

Explanation:

The strategy that I use is inverse operations.

Add 6 to 12, as the equation has "-6". 6+12=18

Now, to find C, we simply divide 18 by 3, as the remaining equation was "3c", which is multiplication.

18/3=6

Therefore, c=6.

To ensure that the answer is correct, plug in the 6 to see if its true.

3(6)-6

18-6=12

User Eray T
by
4.9k points